A wireless power supply EMI suppression method in implantable optogenetic circuits - Ji Yanping; Li Jiawei; Chai Donglin; Zhao Boyan; Zhao Yanran; Wang Shirui; Wang Wensi; Zheng Mengyi (Dianzi Jishu Yingyong)
In this paper, a wireless implantable optogenetic hardware structure is proposed. In the experimental process, a magnetic resonant wireless energy technology is used outside the organism to power the in vivo circuit; however, in the Wireless Energy Transfer (WPT) process, it is necessary to convert the electrical energy at the transmitting end into a high-frequency magnetic field with the help of magnetic coupling, and the magnetic field is the medium for transmitting electrical energy in the wireless energy transfer system, and the Electromagnetic Radiation (EMI) problem brought by it will be a threat to the organism. Therefore, an improved frequency spreading and harmonic suppression wireless energy supply circuit is designed.